An exploratory study of the board composition of European incumbent telecommunication operators - Jason Whalley; Janette Garrett; Pierre Vialle (International Telecommunications Society (ITS), 2015)
While Internet executives such as Jeff Bezos or Mark Zuckerberg have achieved widespread recognition beyond the business pages, this is not the case for the chairman or chief executive officers of telecommunication servicer providers. However, they are responsible for the provision and then management of a key infrastructure that we increasingly rely upon in the information intensive economy that is emerging. An extensive literature has emerged examining the composition of company boards and the impact that they have on the performance of companies. This literature, however, has largely overlooked the telecommunications industry. In this paper we address this shortcoming by presenting an exploratory study of the boards of two European incumbent telecommunication companies: British Telecom and France Télécom / Orange. Through drawing on public documents, we identify the board members of both companies before investigating their characteristics. We focus on the gender, education and professional background of board members as well as their presence on other (company) boards. We conclude by suggesting areas for further research.
Keywords: 330; board composition; telecommunications; BT; France Télécom / Orange